2019
DOI: 10.1111/ajo.13070
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of pregnancy and post‐partum outcomes in women with prolactinoma treated with dopamine agonists

Abstract: Background:In women with prolactinoma medical treatment with dopamine agonists (DA) can restore fertility. A number of studies have established the safety of DA during pregnancy and the impact of pregnancy and lactation on remission of prolactinoma. However, the total number of reported cases remains modest and further evidence is needed. Aims:To evaluate the safety of DA during pregnancy and remission of prolactinoma after pregnancy and lactation. Materials and Methods: Retrospective cohort study (2002-2014) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Recently, postpartum remission rates have been reported to be between 9-36 % in macroprolactinomas [13,14,16,30]. In our study, early postpartum remission was 9.5 %, which was compatible with the above studies and it was increased to 33.3 % in the longterm follow-up.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Recently, postpartum remission rates have been reported to be between 9-36 % in macroprolactinomas [13,14,16,30]. In our study, early postpartum remission was 9.5 %, which was compatible with the above studies and it was increased to 33.3 % in the longterm follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, most of the studies evaluated micro and macroadenomas together. In these studies, advanced maternal age (35-45 years), smaller initial adenoma size, lower PRL levels at diagnosis and postpartum period were reported as the predictors of remission at last follow-up visit [3,6,13,14,16]. Domingue et al [13] reported that normalization of pituitary MRI after pregnancy were independently associated with remission in a retrospective two-center study, which included only 19 macroadenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S.M.O'Sullivan [14] found that Treatment with a DA reestablishes ovulation in over 90% of ladies with prolactinoma and anovulatory fruitlessness and their examination affirms that DA use during the initial five weeks of pregnancy is protected and not related with an expansion in the quantity of unsuccessful labors, intrinsic contortions or other unfavorable neonatal and pregnancy results past populace typical reaches. R.Krysiak [10] found that Both bromocriptine and cabergoline, the two most ordinarily endorsed dopaminergic specialists, share numerous attributes and unfavorable impacts.…”
Section: Discussionmentioning
confidence: 94%
“…Besides, these courses are helpful for patients who might be not able or reluctant to swallow prescription and it is a viable course in the treatment of patients with heaving scenes. For fundamental impacts, the mucous films of the rectum license the ingestion of numerous dissolvable medications [14].…”
Section: Discussionmentioning
confidence: 99%